De novo histoid leprosy in a Colombian patient with multiple skin nodules on the ears and extremities - Lina Marcela Piedrahíta-Rojas; Claudia Juliana Díaz; Kevin Escandón-Vargas (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract Histoid leprosy is an uncommon form of lepromatous leprosy with distinct clinical, histopathological, immunological, and bacteriological features. This variant usually occurs in multibacillary patients who have irregular or inadequate treatment. Herein, we report a case of de novo histoid leprosy diagnosed in a patient from Cali, Colombia. In endemic areas, histoid leprosy should be in the differential diagnosis of any patient presenting with skin nodules. Early diagnosis and appropriate treatment are recommended for mitigating the impact of histoid leprosy cases, which are important reservoirs of Mycobacterium leprae.